المحرض الصّوري - الشمري, . كاظم عبد الله; عنيد, هدى علي (Journal of Legal Sciences, 2019)
Incitement is a from of criminal participation and intended :(The kind of incitement that withholds the instigator .Agitational its activity in oroder to achieve , but interest  is usually achieved  by those assigned to third parties to commit in order to achieve another interest ,which is caught red-handed instigator).      For the induction of the picture for the crimes conditions must  be met the most important activity that is heading the instigator of the picture to third parties for their payment to acting is  a crime and must also be objective stand on crime and catch the culprit Almtalps them , The third   condition boils down to the need to intervene to prevent the instigator check the result of criminal.       Opinions of scholars differ leshan msoalah and the punishment of a person who incites crime figurehead  between those who see the need for punishment and trying to find a pious instigator justifications and save him from punishment